From galloping inflation to price stability in steps: Israel 1985-2013 - Rafi Melnick; Till Strohsal (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
After the introduction of a stabilization program Israeli inflation decreased from 400% in 1985 to 2% in 2013. This paper analyzes how the remarkable transition process of Israel's disinflation took place. We reinforce the existing hypothesis that inflationmoved in distinct steps characterized by constant levels with short-lived fluctuations around them. Multiple endogenous breakpoint tests provide strong empirical evidence in favor of our claim. We find that the disinflation process is defined by three clear steps of high, medium and low inflation. The break dates are in line with major economic events that constitute the end and the beginning of each disinflation step.
Keywords: E31; E52; E58; C22; 330; Inflation; Disinflation Steps; Multiple Breakpoint Tests; Inflation Targeting